Islamic Financial Stability: Previous Research based on Scopus Database - Puspita, Amelia Tri; Shikur, Anwar Adem (Review on Islamic Accounting, 2023)
The global financial system is growing rapidly in a large number of countries in the world, and Indonesia is no exception. The growth of Islamic finance in Indonesia has also experienced a significant increase as indicated by Indonesia's financial assets in the global top ten. The economic crisis a decade ago has accelerated the development process of Islamic finance. These conditions have proven that Islamic finance has a strong enough stability compared to conventional finance. There are still many researchers' contradictions on the stability of Islamic finance. This study aims to determine the development of Islamic Financia l Stability research trends published by leading journals on Islamic financial economics. The data analyzed consisted of 263 indexed research publications. The data is then processed and analyzed using the VoSviewer application to find out the bibliometric map of Islamic Financial Stability research development.